A RETROSPECTIVE STUDY ON IMPORTANCE OF CRP AS A PREDICTOR AND TO ANALYSE THE EFFECTIVENESS OF ANTIBIOTICS IN THE TREATMENT OF NEONATAL SEPSIS AT SECONDARY CARE HOSPITAL OF TIRUPPUR (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Early diagnosis of sepsis in a neonate is often difficult because symptoms and signs are usually non-specific. A study was conducted to evaluate C-reactive protein (CRP) as a screening tool and the effectiveness of antibiotics in the treatment of neonatal sepsis. This retrospective study was conducted at NICU, Government District Headquarters Hospital, Tiruppur from December 2016 to June 2017, on total of 120 neonatal sepsis patients. Patients of Group I received Ampicillin + Gentamicin, Group II received Ampicillin + Gentamicin followed by Cefotaxime + Amikacin, Group III received Cefotaxime + Amikacin, Group IV received Ampicillin + Gentamicin followed by Piptaz followed by Amikacin + Ciprofloxacin and Group V received, Ampicillin + Gentamicin followed by Piptaz then by Amikacin + Meropenem and then by Ciprofloxacin. Chi-square test two side p-value & ONE WAY ANOVA followed by Tukey-Krammer Multiple Comparison Test is used for statistical analysis. Among study subjects, 18 (15%) and 102 (85%) had negative and positive CRP respectively. According to blood culture studies, 15 cases were culture positive, with the following organisms, Klebsiella pneumoniae (53.33%), Escherichia coli (20%), Staphylococcus aureus (20%) and Proteus marbilis (6.66%). Group II is an appropriate choice for empirical therapy of neonatal sepsis and was 46.96% of 66 patients. Group I, which is considered as First Line treatment was 33.33% of 66 patients.